Pengaruh Key Performance Index Terhadap Motivasi Dan Kinerja Karyawan - Muhammad Aditya; Sri Sundari; Marisi Pakpahan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Key Performance Indicator (KPI) is a metric or key indicator used to measure the performance of an organization, department, or individual in achieving set goals and objectives. KPI serves as a tool to evaluate how successfully an entity is achieving its strategic performance targets. This research aims to gain a deep understanding of the concept of Key Performance Indicator (KPI), motivation, and employee performance through a review of scholarly literature. By dissecting information from the literature, this research hopes to provide a strong theoretical foundation and contribute to a practical understanding of the impact of KPI on employee motivation and performance in an organizational context. The contribution of KPI in managing and aligning employee performance becomes a solution in providing information on the extent of success in achieving set work targets, identifying, and monitoring measures of success. Certainly, this is done by demonstrating clear, specific, and measurable performance indicators.